Could nursery rhymes cause violent behaviour? A comparison with television viewing. Issue 12 (19th November 2004) - Davies, P; Lee, L; Fox, A; Fox, E
Abstract : Aims: To assess the rates of violence in nursery rhymes compared to pre-watershed television viewing. Methods: Data regarding television viewing habits, and the amount of violence on British television, were obtained from Ofcom. A compilation of nursery rhymes was examined for episodes of violence by three of the researchers. Each nursery rhyme was analysed by number and type of episode. They were then recited to the fourth researcher whose reactions were scrutinised. Results: There were 1045 violent scenes on pre-watershed television over two weeks, of which 61% showed the act and the result; 51% of programmes contained violence. The 25 nursery rhymes had 20 episodes of violence, with 41% of rhymes being violent in some way; 30% mentioned the act and the result, with 50% only the act. Episodes of law breaking and animal abuse were also identified. Television has 4.8 violent scenes per hour and nursery rhymes have 52.2 violent scenes per hour. Analysis of the reactions of the fourth researcher were inconclusive. Conclusions: Although we do not advocate exposure for anyone to violent scenes or stimuli, childhood violence is not a new phenomenon. Whether visual violence and imagined violence have the same effect is likely to depend on the age of the child and the effectiveness of the storyteller. Re-interpretation of the ancient problem of childhood and youth violence through modern eyes is difficult, and laying the blame solely on television viewing is simplistic and may divert attention from vastly more complex societal problems.